The Netherlands as a Tax Haven for Czech Multinational Corporations - Impact on the Czech Economy - Shuvatov, Nikita; De Castro, Tereza; Zeynalov, Ayaz; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
In an era of a globalised financial environment, multinational corporations (MNCs) use strategic tax differences between nations to reduce tax obligations while increasing their profits. This research examines the phenomenon of profit shifting by Czech multinational corporations to the Netherlands, focusing on quantifying the erosion of the Czech tax base. Drawing on data from the Orbis database, the study employs a specific econometric model to analyse the relationship between reported profits and relevant financial indicators. By examining variables such as EBIT, total assets, and operating revenue, applying regression models and conducting counterfactual analysis, the thesis quantifies the fiscal loss to the Czech Republic from profit-shifting to the Netherlands. The research highlights the Netherlands’ unique position as a conduit jurisdiction. While not a traditional offshore jurisdiction, it offers an advantageous tax environment characterised by a vast treaty network, favourable treatment of intellectual property income, and regulatory mechanisms that facilitate intra-group financing. Czech MNCs utilise various techniques to transfer profits to the Netherlands, including transfer pricing, royalty payments, and intra-group loans. By integrating theoretical insights from the OECD’s BEPS framework, the thesis contextualises the Netherlands’ role in the global tax system. It concludes that profit shifting undermines the Czech Republic’s fiscal sovereignty and social equity, distorts global markets and erodes trust in tax systems.
Vedoucí práce: Tereza De Castro
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses